SLIMS (Senayan Library Management System)-Based Library Management in Improving Students' Reading Skills at Vocational High Schools - Ai Robihatil Milah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to determine how SLiMS (Senayan Library Management System) based library management is implemented in increasing student reading power at SMK Negeri 1 Cijulang. The main focus of this research includes how the process of planning, organizing, implementing, and evaluating library management is carried out by utilizing the SLiMS system as a digital media that facilitates the management of library information systematically and efficiently. Efforts to increase student reading power are an important background in this study, given the low interest in reading among students which is still a challenge in today's digital era. This research uses a qualitative method with a case study type. The subjects in this study include the head of the library, service technicians, reading technicians, and students as key informants. Data collection was done through interviews, observation, and documentation. This method was chosen to explore data comprehensively, deeply, and in accordance with the real conditions in the field. The data analysis technique used in this research refers to the Miles and Huberman model, which goes through three main stages: data reduction, data presentation, and conclusion drawing/verification.The results showed that the use of SLiMS has had a positive impact on the efficiency of library management, easy access to information, and student interest in utilizing library services. However, there are still some obstacles such as the unavailability of electronic books and the absence of a structured permanent literacy program. Therefore, strengthening literacy programs and procuring digital collections are important recommendations to improve students' literacy culture in a sustainable manner.